2020
DOI: 10.1186/s13578-020-00386-3
|View full text |Cite
|
Sign up to set email alerts
|

Insights into superoxide dismutase 3 in regulating biological and functional properties of mesenchymal stem cells

Abstract: Mesenchymal stem cells (MSCs) have been extensively studied and implicated for the cell-based therapy in several diseases due to theirs immunomodulatory properties. Embryonic stem cells and induced-pluripotent stem cells have either ethical issues or concerns regarding the formation of teratomas, introduction of mutations into genome during prolonged culture, respectively which limit their uses in clinical settings. On the other hand, MSCs also encounter certain limitation of circumscribed survival and reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…A secretory extracellular enzyme, SOD3 is one of the most important antioxidants in mammals [ 24 ]. We have previously shown its therapeutic potential in many inflammatory diseases; however, since the half-life of SOD3 is short, it is limited in its use as a therapeutic substance by itself.…”
Section: Discussionmentioning
confidence: 99%
“…A secretory extracellular enzyme, SOD3 is one of the most important antioxidants in mammals [ 24 ]. We have previously shown its therapeutic potential in many inflammatory diseases; however, since the half-life of SOD3 is short, it is limited in its use as a therapeutic substance by itself.…”
Section: Discussionmentioning
confidence: 99%
“…The development of SOD3-overexpressing MSCs is being investigated in this field. The aim here is to overcome the limits of MSC therapy, such as circumscribed survival and reduced immunomodulatory potential, using the benefits of SOD3 antioxidant and immunomodulatory activity [ 304 ]. Future studies will provide more in-depth knowledge of the feasibility of this strategy.…”
Section: Sod Sourcesmentioning
confidence: 99%
“…On the other hand, no significant influence on the RNA expression of the other antioxidant enzymes (SOD2 and HMOX1) was revealed. All enzymes studied are significant components of the antioxidant defense system, since superoxide dismutases (SODs) detoxify the superoxide radicals into hydrogen peroxide and oxygen [ 33 ], glutathione peroxidase 1 (GPX1) catalyses the reduction of H2O2 or organic hydroperoxides to water or the corresponding alcohols [ 34 ], and heme oxygenase 1 (HMOX1) catalyses the first step of the oxidative degradation of the heme group and is involved in the suppression of the inflammatory response [ 35 ]. It could be concluded that selected antioxidant responses were induced to eliminate reactive oxygen species and protect cells against destruction caused by oxidative stress.…”
Section: Discussionmentioning
confidence: 99%